(untitled) (CIPEEX, 2026)
This study investigated the contributions of digital games to literacy and digital literacy in conjunction with critical environmental education, focusing on the Cerrado biome. The research, which adopted a qualitative approach and theoretical-propositional approach, was based on a literature review and document analysis, including classical and contemporary authors—such as Piaget (1976), Vygotsky (2001), Freire (1996), Rivoltella (2012), Soares (2002), Sauvé (2005), Guimarães (2012), and Vicente (2025)—as well as normative documents such as the BNCC (2018/2022). The results indicate that digital games, when integrated in a planned and intentional manner into pedagogical practices, promote meaningful, interdisciplinary, and contextualized learning by developing cognitive, socioemotional, and ecological skills. The analysis allowed us to systematize a set of examples into a table, highlighting the pedagogical potential of different digital resources for developing ecological and digital subjects. The conclusion is that the critical use of digital games in schools increases student engagement, strengthens digital and ecological literacy, and contributes to the appreciation of the Cerrado as a collective heritage. We recommend expanding pedagogical practices that integrate digital culture and sustainability, as well as continuing teacher training for the conscious and creative use of these technologies.